Dissolved Nitrogen Acquisition in the Symbioses of Soft and Hard Corals With Symbiodiniaceae: A Key to Understanding Their Different Nutritional Strategies? - Pupier, Chloé A.; Grover, Renaud; Fine, Maoz; Rottier, Cécile; van de Water, Jeroen A. J. M.; Ferrier-Pagès, Christine (Frontiers in Microbiology, 2021)
Nitrogen is one of the limiting nutrients for coral growth and primary productivity. Therefore, the capacity of different associations between corals and their algal symbionts (Symbiodiniaceae) to efficiently exploit the available nitrogen sources will influence their distribution and abundance. Recent studies have advanced our understanding of nitrogen assimilation in reef-building scleractinian (hard) coral-Symbiodiniaceae symbioses. However, the nutrient metabolism of other coral taxa, such as Alcyoniina (soft corals), remains underexplored. Using stable isotope labeling, we investigated the assimilation of dissolved nitrogen (i.e., ammonium, nitrate, and free amino acids) by multiple species of soft and hard corals sampled in the Gulf of Aqaba in shallow (8-10 m) and mesophotic (40-50 m) reefs. Our results show that dissolved nitrogen assimilation rates per tissue biomass were up to ten-fold higher in hard than in soft coral symbioses for all sources of nitrogen. Although such differences in assimilation rates could be linked to the Symbiodiniaceae density, Symbiodiniaceae species or the C:N ratio of the host and algal symbiont fractions, none of these parameters were different between the two coral taxa. Instead, the lower assimilation rates in soft coral symbioses might be explained by their different nutritional strategy: whereas soft corals may obtain most of their nitrogen via the capture of planktonic prey by the coral host (heterotrophic feeding), hard corals may rely more on dissolved nitrogen assimilation by their algal symbionts to fulfill their needs. This study highlights different nutritional strategies in soft and hard coral symbioses. A higher reliance on heterotrophy may help soft corals to grow in reefs with higher turbidity, which have a high concentration of particles in suspension in seawater. Further, soft corals may benefit from lower dissolved nitrogen assimilation rates in areas with low water quality.